The Impact of Transformational Leadership on Employees’ Job Embeddedness : Pasha Bank OSCJ Case - Rzayeva, Aytaj (ADA University, 2022)
The purpose of this study is to ascertain how transformational leadership affects job embedding. Employees of the Pasha Bank OJSC were voluntarily asked to participate in a survey for this reason. IBM SPSS statistical software was used to examine the information gathered from the 72 survey participants. The study's hypotheses were tested using regression analysis and an independent sample T-test. This investigation shows that male employees are more involved than female employees, with female employees having a lower mean view on job embeddedness than male employees. To gauge the impact of transformative leadership on employee’s job embeddedness, linear regression analysis was used. This study revealed that the adjusted R squared value was 0.271. This figure indicates that transformational leadership behaviors of managers account for 27.1% of the variance in workers' job embeddedness behaviors. The impact of idealized influence, individualized care, intellectual stimulation, and inspiring motivation—the sub-dimensions of transformational leadership—on job embeddedness has been investigated. The regression study found that idealized effect explained 23.8% of job embeddedness, followed by individual attention at 14.9%, intellectual stimulation at 19.2%, and inspiring motivation at 28.3%.
Keywords: Transformational leadership; Job embeddedness; Pasha Bank OJSC; Business